2(-6n+1)=-94

Simple and best practice solution for 2(-6n+1)=-94 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-6n+1)=-94 equation:


Simplifying
2(-6n + 1) = -94

Reorder the terms:
2(1 + -6n) = -94
(1 * 2 + -6n * 2) = -94
(2 + -12n) = -94

Solving
2 + -12n = -94

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -12n = -94 + -2

Combine like terms: 2 + -2 = 0
0 + -12n = -94 + -2
-12n = -94 + -2

Combine like terms: -94 + -2 = -96
-12n = -96

Divide each side by '-12'.
n = 8

Simplifying
n = 8

See similar equations:

| -16=4(a-3) | | 3/8-1/6= | | 6a+4-9a=10-a | | 6x-3y=-72 | | -8(3-8k)=104 | | -2x+7x+30=15 | | 5x-31=4x-10 | | 5x-3q=4x-10 | | 6h+5=-30-h | | 8x^6+5x^3+1=0 | | 1/8x-y=7 | | (3a^2+5a-4)-(3a^2-4a+1)=4a+15 | | 5(3-2n)=85 | | 9-2x-9-16x=14x-7-4x-11 | | 19x+-9x+-11=19 | | 3g+26=g+10 | | 4(4x-3)=100 | | -9(y+1)=3(y-3)-36 | | pr+qs=4 | | 0.1888888888888888888888888888888888= | | 37.68=(2)(3.14)(x+1) | | -5(2x-3)-5x=120 | | 8-3(x+4)=2x+1 | | -3(4-7x)=93 | | 7n+12=.50(14n+24) | | 90-x=1/5(180-x) | | 2V+7=5 | | 2x+7-7x=-33 | | 171/90 | | 1-9n^2=-124 | | x+9+x=79 | | 10x-75=-25x+275 |

Equations solver categories